2014
DOI: 10.1074/mcp.m113.031336
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Soluble Modulin (PSM) Variants of Community-Associated Methicillin-Resistant Staphylococcus aureus (MRSA) Captured Using Mass Spectrometry-Based Molecular Networking

Abstract: Molecular genetic analysis indicates that the problematic human bacterial pathogen methicillin-resistant Staphylococcus aureus possesses more than 2000 open reading frames in its genome. This number of potential gene products, coupled with intrinsic mechanisms of posttranslational modification, endows methicillin-resistant Staphylococcus aureus with a highly complex biochemical repertoire. Recent proteomic and metabolomic advances have provided methodologies to better understand and characterize the biosynthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…78 Intriguingly, treatment of S. aureus with antibiotics leads to the production of PSM structural variations via truncation of the peptide and amino acid substitutions. 77 Production concentrations of PSMs are much lower from the S. aureus related commensal species Staphylococcus epidermidis , explaining its reduced virulence. 81 It has been suggested that some strains of S. epidermidis may inhibit potential pathogens by enhancing production of human antimicrobial peptides.…”
Section: Natural Products In Human Diseasementioning
confidence: 99%
“…78 Intriguingly, treatment of S. aureus with antibiotics leads to the production of PSM structural variations via truncation of the peptide and amino acid substitutions. 77 Production concentrations of PSMs are much lower from the S. aureus related commensal species Staphylococcus epidermidis , explaining its reduced virulence. 81 It has been suggested that some strains of S. epidermidis may inhibit potential pathogens by enhancing production of human antimicrobial peptides.…”
Section: Natural Products In Human Diseasementioning
confidence: 99%
“…Although originating from different organisms, PSMα3 and hLL-37 display sequence homology, particularly in their core region ( Fig. S1) and are cleaved in-vivo into active derivatives (36)(37)(38)(39)(40)(41)(42). Many hLL-37 derivatives show a diverse array of selectivity against microbial strains, and additional functions within the immune system (26,36,37,43,44).…”
mentioning
confidence: 99%
“…Recently, our group used the platform to build a molecular network representative of extracellularly released, small molecular weight biosynthetic factors produced by MRSA (Gonzalez et al, 2014). Here, we report the continued examination of the created molecular network by de novo sequencing and peptidogenomic approaches (Kersten et al, 2011), recovering peptides pertaining to the AgrD N-terminal domain ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…PSMs are cytolytic, formylated and non-formylated peptide variants that are upregulated in community-associated MRSA and genetically linked to the agr system (PSMγ is embedded within RNA III) (Wang et al, 2007; Gonzalez et al, 2014). Because of the structural similarities between peptides, N-AgrD could play a potential role in biofilm structural formation as demonstrated for PSMs (Periasamy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%